The queen and the bird: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story revolves around a kind queen who encounters a beautiful bird and learns important lessons about compassion and freedom. Through her interaction with the bird, she discovers the value of empathy and the impact of kindness on both her life and those around her.